Sacred matter: animacy and authority in the Americas - Kosiba, Steve; Janusek, John Wayne; Cummins, Thomas B. F. (Dumbarton Oaks Pre-Columbian symposia and colloquia, 2020)
The nature of the world, the stuff of politics: exploring animacy and authority in the indigenous Americas /Steve Kosiba --Chiefly jaguar, chiefly tree: mastery and authority in the Upper Xingu /Carlos Fausto --Soul proprietors: durable ontologies of Maya deep time /Patricia A. McAnany --Burning sorrow: engaging the animacy of social-ecological life processes in native Amazonian death rituals /Beth A. Conklin --Descartes, Jesus, and Huitzilopochtli: ontologies /Byron Ellsworth Hamann --"Metaphysical subtleties and theological niceties": incarnation, incantations, animism, and the powers of Pre-Columbian visual imagery /Thomas B. F. Cummins --The Lanzón's tale /Mary Weismantel --Cosmopolitical bodies: living monoliths, vital tectonics, and the production of Tiwanaku /John Wayne Janusek --On the threshold of the huaca: sanctuaries of sound in the ancient Andean world /Marco Curatola Petrocchi --Buried alive: buildings, authority, and gradients of being in Northern Yucatan, Mexico /Scott Hutson, Jacob Welch, Shannon Plank, and Barry Kidder --Animating public buildings in Formative Period Oaxaca: political and ontological implications /Arthur A. Joyce --The material ambivalence of health and spirituality in colonial northeastern New Spain /Diana DiPaolo Loren --Southern Quechua ontology /Bruce Mannheim --Purpose, belief, and political action in the Sierra Nevada de Santa Marta /Santiago Giraldo --Shifts in the light: a journey through varied perspectives on animacy and authority in the Americas /Catherine J. Allen.